A Preconcentrating Lab-on-a-Chip Device Targeted Towards Nanopore Sensors - Kean, Kaitlyn (Université d'Ottawa / University of Ottawa, 2020)
Continuous progress in the nanotechnology field has allowed for the emergence of powerful, nanopore-based detection technology. Solid-state nanopores were developed for next-generation sequencing and single-molecule detection. They are advantageous over their biological counterpart because they offer robustness, stability, tunable pore size and the ability to be integrated within a microfluidic device. With all of these attractive attributes, solid-state nanopores are a top contender for point-of-care diagnostic technologies. However, hindering their performance is an inability to distinguish between small molecules, pore-clogging, and the detection rate's dependence on sample concentration. The concentration-dependent detection rate becomes particularly evident at low sample concentrations (<1 nM), sometimes taking hours for the nanopore to sense a single molecule because of diffusion. The inability to distinguish between small molecules can be addressed using DNA nanostructures; however, pore-clogging and variable detection rates hinder its potential in a clinical setting. This thesis proposes a microfluidic device design and methodology that seeks to mitigate pore-clogging and improve the detection rate for dilute samples. DNA coated microbeads will create a bead column within the microfluidic device and confine the target molecules to an extremely small (20 nL) volume. The sample can be washed, ridding the contaminants, and eluted on-chip, so the sample is purified and concentrated, affording a more reliable sensing performance. First, a magnetic microbead DNA assay was optimized off-chip, and the capture and release efficiencies were monitored using a Biotek™ Epoch™ 2 spectrophotometer (Chapter 2). Next, a novel microfluidic device design was optimized and validated to ensure precise sample manipulation (Chapter 3). Finally, the microbead assay was incorporated into the microfluidic device for sample concentration (Chapter 4). Fluorescence microscopy results suggest successful DNA elution from the microbeads within the microfluidic device, allowing for a 28.5 X concentration increase. This platform shows promise for sample preconcentration by reducing the starting DNA sample volume of 25 µL to 20 nL, which could improve the speed of solid-state nanopore sensing.
Keywords: Nanopore; Microfluidics; Lab-on-a-chip; Preconcentration